Comment on Renormalization Group Study of the A+B->0 Diffusion-Limited Reaction - Lee, B; Cardy, J (1996)
A recent argument of Oerding shows that our calculation of the quantity Delta, which determines the amplitude of the asymptotic decay of the particle density in d < 2 < 4, was in error. Instead it is simply given by Delta = n_0, the initial density, for uncorrelated initial conditions.